2022
DOI: 10.1002/cam4.5345
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives surrounding fertility preservation and posthumous reproduction for adolescent and young adults with terminal cancer: Survey of allied health professionals

Abstract: Background While all reproductive‐aged individuals with cancer should be offered fertility preservation (FP) counseling, there is little guidance over offers to adolescent and young adults (AYA) with terminal diagnoses, especially when considering posthumous assisted reproduction (PAR). The Enriching Communication skills for Health professionals in Oncofertility (ECHO/ENRICH) trains Allied Health Professionals (AHPs) to improve communication with AYAs with cancer. Little is known about AHPs' role in assisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In light of these ethical and psychological considerations for PAR in the context of grief, providers will want to be thoughtful about how to best support these families of AYA with poor cancer prognosis. Previous research has found that many allied health professionals feel uncomfortable discussing fertility preservation and PAR in the context of AYA with poor cancer prognosis, which can result in avoidance of these topics, and ultimately, lead to inadequate support for patients and their families (Barrett et al, 2023). The first step in addressing the ethical and psychological concerns for PAR in the context of grief is improving professionals’ comfort and competence with fertility preservation and PAR as well as their ability and comfort communicating about these topics, which can be developed through provider training, such as ECHO/ENRICH (Barrett et al, 2023; Vadaparampil et al, 2016).…”
Section: Clinical Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these ethical and psychological considerations for PAR in the context of grief, providers will want to be thoughtful about how to best support these families of AYA with poor cancer prognosis. Previous research has found that many allied health professionals feel uncomfortable discussing fertility preservation and PAR in the context of AYA with poor cancer prognosis, which can result in avoidance of these topics, and ultimately, lead to inadequate support for patients and their families (Barrett et al, 2023). The first step in addressing the ethical and psychological concerns for PAR in the context of grief is improving professionals’ comfort and competence with fertility preservation and PAR as well as their ability and comfort communicating about these topics, which can be developed through provider training, such as ECHO/ENRICH (Barrett et al, 2023; Vadaparampil et al, 2016).…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…Previous research has found that many allied health professionals feel uncomfortable discussing fertility preservation and PAR in the context of AYA with poor cancer prognosis, which can result in avoidance of these topics, and ultimately, lead to inadequate support for patients and their families (Barrett et al, 2023). The first step in addressing the ethical and psychological concerns for PAR in the context of grief is improving professionals’ comfort and competence with fertility preservation and PAR as well as their ability and comfort communicating about these topics, which can be developed through provider training, such as ECHO/ENRICH (Barrett et al, 2023; Vadaparampil et al, 2016). These trainings uphold APA ethical principles as a measure to improve care, reduce misinformation, increase accessibility of knowledgeable providers, and promote the informed consent of AYA and families.…”
Section: Clinical Recommendationsmentioning
confidence: 99%